Energy Efficiency of Municipalities in the Republic of Macedonia - Kuzmanovska М., Lazarevska A. M. (Centre for Regional Policy Research and Cooperation Studiorum, Skopje (мкд. Центар за регионални истражувања и соработка „Студиорум”, Скопје), 2017)
The Republic of Macedonia is continuously working on increasing the renewable energy sources and improving the energy efficiency. The purpose of this analysis is to understand the situation related to the advances in implementing the energy efficiency programs at local level. The programs submitted to EARM were analyzed with regards to number of programs submitted for three consecutive years. The obtained results indicate a trend of improvement in the application of the positive legal regulations, and although the obligation for energy efficiency programs came into force in 2011, three years later 30 % of municipalities have not yet submitted a program. In the near future, it is suggested that local communities dedicate more attention to this issue, thus to contribute towards successful implementation of the Strategy for Developing Energy Efficiency until 2020 in the Republic of Macedonia, and as a result, to contribute to reducing the consumption of energy resources, which directly and indirectly contributes to overall environmental protection.
Keywords: energy efficiency, energy management, municipalities